Structure and language features of University lecture introductions - Yeo, Jiin Yih. (Universiti Malaysia Sarawak, (UNIMAS), 2011)
The case study examined the spoken discourse in lecture introductions for core courses in an institution of higher learning in Malaysia. The objectives of the study were to (1) determine the structure of lecture introductions; (2) identify the frequencies of the types of personal pronouns used by the lecturers to active students' prior knowledge; and (3) analyse the types and functions of questions asked by the lecturers during lecture introductions, and student responses to these questions. Forty-seven lecture introduction sessions were audiotaped and analysed based on Schuck's (1970), Davies's (1981), Rounds's (1985; 1987a; 1987b) and Athanasiadou's (1991) framewoks.